Quantum Dot-Based Nanoparticles in Targeted Cancer Therapy: Advances in Medical Physics Applications - Azzouz, Ali Musa Abdulreda; Naima, Hanan jwaid rafea; Kadhim Obaid, Hassan Diab; abed khadir, Ghaith oudah (American Journal of Botany and Bioengineering, 2025)
Quantum dot (QD)-based nanoparticles have emerged as transformative agents in targeted cancer therapy due to their unique optical, chemical, and size-dependent properties. Despite significant progress in QD synthesis, imaging, and surface functionalization, challenges remain in achieving clinical-grade safety, precise delivery, and long-term biocompatibility. This review synthesizes interdisciplinary research on the design, functionalization, and application of QDs in diagnostics, photodynamic therapy, and drug delivery, with emphasis on medical physics innovations. The study evaluates both in vitro and in vivo findings, including QD conjugation with aptamers, antibodies, and therapeutic agents for site-specific drug release. Key implications suggest that while QD-based systems hold immense potential for theranostics and minimally invasive oncology interventions, future research must address regulatory approval, toxicity mitigation, and scalable synthesis methods to ensure safe and widespread clinical adoption.